The Impact of Stress Stability on Job Satisfaction and the Quality of Human Capital - Rudaleva, Irina A.; Mustafin, Askar N. (Journal of History Culture and Art Research, 2017)
Long professional stress has a significant impact on the psychological state of employees that inevitably affects the activities of any organization. Therefore, at present, more and more attention is being paid to minimize the negative consequences of stressful staff conditions, with the help of specific procedures of stress management. In this paper, we investigated the impact of stress, the types of stress-resistance of staff individual, and the influence of stress on the degree of job satisfaction of bank employees. The study concludes that the following factors affect the level of job satisfaction of bank employees: wage satisfaction, the level of stress at the workplace, and the relationships in the team. The main factor of the bank employees stress is a large amount of work and a short time period for doing the work.